Relationship Stress Levels with Menstrual Cycle in Adolescent Girls - Anjarsari, Nurul; Sari, Etika Purnama (Universitas Airlangga, 2020)
Introduction: Psychological changes in adolescence can affect adolescent emotions that can cause stress. Stress in adolescent one of which can disrupt the menstrual cycle. The purpose of this study was to determine the relationship of stress levels with the menstrual cycle in adolescents.Method: his study uses a cross sectional approach. The sample in this study was 92 adolescents of Wachid Hasyim 1 Surabaya High School who were taken by using Simple Random Sampling technique. Instrument for collecting stress levels using the DASS 42 Questionnaire and menstrual cycle questionnaire.Results: . This study tested using Chi-Square correlation test. Chi-Square correlation test results obtained p-value = .016. This means that there is a relationship between stress levels and the menstrual cycle.Conclusion: There are various factors related to irregular menstrual cycles in adolescents where one of them is stress. Further study needs to be conducted related to the impact of stress on other menstrual problems such as duration, dysmenorrhea and others to further understand the impact of stress on menstrual problems in adolescents.